Educating on the Application of Tensorflow in Artificial Intelligence, Machine Learning and Deep Learning - Santoso, Ilham Budi; Aji, Irfan Pandu; Franskusuma, Sutio; Putri, Khansa Aqila; Ardharani, Yana; Mujiastuti, Rully; Nurbaya Ambo, Sitti; Meilina, Popy; Rosanti, Nurvelly; Amri, Nurul (Edumedia Solution, 2025)
In addition to bringing positive impacts, technological developments also provide new challenges in improving people's technological literacy, especially related to Artificial Intelligence (AI), Machine Learning (ML), and Deep Learning (DL). One of the main challenges is the low public understanding of these technologies, which are increasingly relevant in the era of digital transformation. On the other hand, Google developed a library with the name TensorFlow which is widely used for data processing in Artificial Intelligence, Machine Learning, and Deep Learning. Based on this, educational activities were carried out in the form of introducing and training the use of TensorFlow to the general public in the form of webinars and workshops with the theme ‘Introduction to TensorFlow for Artificial Intelligence, Machine Learning, and Deep Learning’. The activity was carried out in two stages, namely webinars for delivering basic material and workshops for hands-on practice. Based on evaluation through a Likert scale questionnaire, the majority of participants stated that they were very satisfied with the quality of the material, presenters, and implementation of activities. The post-test results also showed an increase in participants' understanding of the material, as evidenced by correct answers on topics such as TensorFlow functions, supervised learning, and neural networks. The participation of 52 participants from various institutions shows the success of this activity in achieving its goals.